2013
DOI: 10.1016/j.bjid.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of CTX-M producing Enterobacteriaceae isolated from bloodstream infections in Rio de Janeiro, Brazil: emergence of CTX-M-15

Abstract: Ninety-three isolates were screened as ESBL positive and 85 (91%) were found to carry CTX-M-type, as follows: K. pneumoniae 59 (49%), E. cloacae 15 (42%), and E. coli 11 (15%). Ten isolates resistant for carbapenems in K. pneumoniae were blaKPC-2 gene positive. Among CTX-M type isolates, CTX-M-15 was predominant in more than 50% of isolates for K. pneumoniae, E. coli, and E. cloacae. PFGE analysis of CTX-M producing isolates showed the predominance of CTX-M-15 in 10 of 24 pulsotypes in K. pneumoniae, 6 of 13 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
4
23
1
2
Order By: Relevance
“…In our study, ESBL production was detected in different genera, with an overall prevalence of 30.3% in the strains tested and the majority of positive isolates belonging to Enterobacter sp., Escherichia coli, and Klebsiella sp. Similar percentages were reported in other studies conducted by Seki et al (14) (40.2%), Lenhard-Vidal et al (15) (16) was conducted at the same hospital as the present study.…”
Section: Ethical Considerationssupporting
confidence: 92%
“…In our study, ESBL production was detected in different genera, with an overall prevalence of 30.3% in the strains tested and the majority of positive isolates belonging to Enterobacter sp., Escherichia coli, and Klebsiella sp. Similar percentages were reported in other studies conducted by Seki et al (14) (40.2%), Lenhard-Vidal et al (15) (16) was conducted at the same hospital as the present study.…”
Section: Ethical Considerationssupporting
confidence: 92%
“…24 In Brazil, several studies have shown that CTX-M-15 is one of the most frequent ESBLs and is widely distributed in the country. 25 In Peru, limited investigations have included the molecular characteristics of Klebsiella, however, CTX-M-2 and CTX-M-15 were observed among commensal E. coli from healthy children in 2002. 26 This study has several limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Isolates producing bla CTX-M-15 and bla SHV-11 have also been reported in Singapore (18). Furthermore, the coproduction of KPC-2 and CTX-M-15 has been described in K. pneumoniae ST437 (clonal complex 11) isolated from patients with bloodstream infections in Brazil (19).…”
mentioning
confidence: 95%